EFEKTIVITAS STRATEGI DALAM PENGELOLAAN KELAS DI SMPN 1 WONOREJO PADA GENERASI Z - Agus Qowiyuddin; Farda Faidah (Universitas Nahdlatul Ulama Pasuruan, 2023)
This research aims to identify trends in successful classroom management by generation Z, as well as study teachers strategies over the past 2 years. The results showed that the average Z class is more dominated by the way teachers and students manage it. The study used a qualitative, literature-based, research approach. The review of several studies found that the main problem lies in the preparation, struggle and management, process and final result for self-evaluation in teaching. However, it should be emphasized that teachers must understand the problem-based learning model. Generation Z is very critical and likes to argue, so it needs to understand problem-based learning models, presentations and group debates in class can be an effective way to stimulate their interest in learning.